Innate Immune System and Preeclampsia - Perez-Sepulveda, Alejandra; Torres, Maria Jose; Khoury, Maroun; Illanes, Sebastian E. (Frontiers in Immunology, 2014)
Normal pregnancy is considered as a Th2 type immunological state that favors an immune-tolerance environment in order to prevent fetal rejection. PE has been classically described as a Th1/Th2 imbalance; however, the Th1/Th2 paradigm has proven insufficient to fully explain the functional and molecular changes observed during normal/pathological pregnancies. Recent studies have expanded the Th1/Th2 into a Th1⁄Th2⁄Th17 and regulatory T (Treg) cells paradigm and where dendritic cells could have a crucial role. Recently, some evidence has emerged supporting the idea that mesenchymal stem cells might be part of the feto-maternal tolerance environment. This review will discuss the involvement of the innate immune system in the establishment of a physiological environment that favors pregnancy and possible alterations related to the development of preeclampsia.